Non-targeting siRNA-mediated responses are associated with apoptosis in chemotherapy-induced senescent skin cancer cells - Betlej, Gabriela; Błoniarz, Dominika; Lewińska, Anna; Wnuk, Maciej (Chemico-Biological Interactions, 2023)
It is widely accepted that siRNA transfection can promote some off-target effects in the genome; however, little is known about how the cells can respond to the presence of non-viral dsRNA. In the present study, non-targeting control siRNA (NTC-siRNA) was used to evaluate its effects on the activity of pathogen and host-derived nucleic acid-associated signaling pathways such as cGAS-STING, RIG-I, MDA5 and NF-κB in A431 skin cancer cells and BJ fibroblasts. NTC-siRNA treatment promoted cytotoxicity in cancer cells. Furthermore, NTC-siRNA-treated doxorubicin-induced senescent cancer cells were more prone to apoptotic cell death compared to untreated doxorubicin-induced senescent cancer cells. NTC-siRNA stimulated the levels of NF-κB, APOBECs, ALY, LRP8 and phosphorylated STING that suggested the involvement of selected components of nucleic acid sensing pathways in NTC-siRNA-mediated cell death response in skin cancer cells. NTC-siRNA-mediated apoptosis in cancer cells was not associated with IFN-β-based pro-inflammatory response and TRDMT1-based adaptive response. In contrast, in NTC-siRNA-treated fibroblasts, an increase in the levels of RIG-I and IFN-β was not accompanied by affected cell viability. We propose that the use of NTC-siRNA in genetic engineering may provoke a number of unexpected effects that should be carefully monitored. In our experimental settings, NTC-siRNA promoted the elimination of doxorubicin-induced senescent cancer cells that may have implications in skin cancer therapies.
Keywords: Apoptosis; Doxorubicin; Non-targeting control siRNA; Nucleic acid sensing; Senescence; Skin cancer